Translation Errors in Subtitle of the Movie Joker 2019 on Netflix - Arina Haque; Happy Cruzia Rini (Humanitatis : Journal of Language and Literature, 2023)
There have been various genres of movies completed with their subtitles. The role of subtitle is crucial, besides gaining engagement with the audience, subtitle also conveys the meaning and the message of the movie. However, there have been found errors in the subtitle itself. This study aims to discover the types of translation errors in the English-Indonesian language pair of the Joker (2019) movie shown on Netflix. The English-Indonesian subtitles were used as the data for the study. The method of the study is qualitative descriptive and The American Translators Association (ATA) framework errors category was applied in analyzing the error types. The results showed that there were six types of errors; (1) omission errors; (2) misunderstanding errors; (3) faithfulness errors; (4) literalness errors; (5) ambiguity errors and (6) other errors that do not include in the category. The most frequent error is omission, misunderstanding, and faithfulness errors. All the errors found influenced the information and message delivered to the viewers.